2022
DOI: 10.1021/acsami.2c13309
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional Strategy: Ammonium Citrate-Modified SnO2 ETL for Efficient and Stable Perovskite Solar Cells

Abstract: The tin oxide (SnO2) electron transport layer (ETL) plays a crucial role in perovskite solar cells (PSCs). However, the heterogeneous dispersion of commercial SnO2 colloidal precursors is far from optimized, resulting in dissatisfied device performance with SnO2 ETL. Herein, a multifunctional modification material, ammonium citrate (TAC), is used to modify the SnO2 ETL, bringing four benefits: (1) due to the electrostatic interaction between TAC molecules and SnO2 colloidal particles, more uniformly dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The charge recombination resistance ( R rec ) is raised from 974.2 Ω to 1940.4 Ω compared to the pristine device, indicating effective electron–hole recombination reduction due to defect suppression, which complementarily explains the change in the perovskite photovoltaic device's performance characteristics. 22,35,36 In addition, EIS shows that the series resistance ( R s ) in the modified C-PSCs is 25.4 Ω, lower than 34.2 Ω obtained for the pristine C-PSCs, indicating lower current losses at the interfaces of the modified C-PSCs. Indeed, the FF and J SC improvements can be attributed to the boosted perovskite film quality, reduced non-radiative recombination, and facilitated charge extraction.…”
Section: Resultsmentioning
confidence: 91%
“…The charge recombination resistance ( R rec ) is raised from 974.2 Ω to 1940.4 Ω compared to the pristine device, indicating effective electron–hole recombination reduction due to defect suppression, which complementarily explains the change in the perovskite photovoltaic device's performance characteristics. 22,35,36 In addition, EIS shows that the series resistance ( R s ) in the modified C-PSCs is 25.4 Ω, lower than 34.2 Ω obtained for the pristine C-PSCs, indicating lower current losses at the interfaces of the modified C-PSCs. Indeed, the FF and J SC improvements can be attributed to the boosted perovskite film quality, reduced non-radiative recombination, and facilitated charge extraction.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, choosing the best‐suited ETL is crucial in optimizing PSCs’ PCE. [ 39 ] Some of the remarkable PSCs and their device structure and performance parameters are presented in Table 1 .…”
Section: Essential Components Of Perovskite Solar Cellmentioning
confidence: 99%
“…[15] Figure 1b shows that both films from the pristine SnO 2 and the PAA modified SnO 2 precursors exhibited fine optical transmittance in the range from 400 to 800 nm, and the fine optical transmittance of ETLs are favorable for the light absorption of the perovskite layer. Meanwhile, the atom force microscopy (AFM) showed that the root-mean-square roughness (R q ) slightly increased from 2.42 to 2.79 nm (Figure 1c and 1d), the increased roughness of the PAA modified SnO 2 films may facilizing the nucleation and growth of perovskite films, [28] while decreasing the contact between ETL and perovskite.…”
Section: Optical Electrochemical Propertiesmentioning
confidence: 99%